Contribution of Philosophy of Science in Scientific Research: An Epistemological and Methodological Review - Agung Setiabudi; Ahmad Syukri; Badarussyamsi (International Journal of Education, Language, and Social Science, 2025)
Scientific research requires not only systematic empirical techniques but also a robust theoretical and philosophical foundation to ensure methodological rigor and validity. This study examines the historical and functional contributions of the philosophy of science to modern research methodology and paradigms across four distinct eras: Classical, Renaissance, Modern, and Contemporary. Utilizing a qualitative library research design combined with content analysis and historical-hermeneutic interpretation, this paper evaluates how evolving philosophical frameworks shape scientific inquiry. The findings demonstrate that philosophy provides the fundamental ontological, epistemological, and axiological pillars that govern research designs, transitioning scientific practice from medieval dogmatism to empirical observation, logical positivism, and ultimately contemporary pluralism. Furthermore, the study illustrates how philosophical reflection directly informs modern methodologies such as big data analytics, artificial intelligence ethics, and interdisciplinary collaboration by fostering critical reflectivity, operational transparency, and ethical accountability. By bridging historical philosophical developments with contemporary socio-technological practices, this research offers a comprehensive framework for embedding epistemological flexibility into modern research governance and scientific education